(untitled) (Vietnam Journal of Community Medicine, 2023)
Objectives: To evaluate the training of some core competencies of the master of nursing in Vietnam. Subjects and Methods: 240 masters of nursing were enrolled in a cross-sectional and descriptive study with convenience sampling method. These nurses autofilled the survey form on google form in order to evaluate their training in core competencies based on a 5-point Likert scale with 4 groups of core competencies (Nursing professional competency; nursing management and professional development; practice - making legal policy and professional ethics; and training and scientific research). Results: According to the respondents, 4 groups of core competencies with 38 specific skills had high average score and passing rate. These 38 items in four groups of competencies were arranged appropriately, meeting the requirements of high internal consistency. Conclusion: The content related to 4 groups of research competencies and 38 detailed competencies has been taught in the master’s programs with different degrees, but not yet clearly specified for each individual content. Therefore, the groups of core and detailed competencies should be included in the output standards of the master’s degree nursing training program.